Beauty Concept in Pond’s Advertisements: A Critical Discourse Analysis - Pelita Hati Barus (Talenta Publisher, 2021)
This research aimed at analyzing the beauty concept in Pond’s advertisements based on three-dimensional models of discourse in Fairclough’s Critical Discourse Analysis (CDA) framework. This research uses a qualitative method to analyze the beauty concept in Pond’s advertisements.The results of this study show that the language used in Pond’s advertisements appear very interesting in building image to the viewers and were successful in using the various discourse strategies to attract people’s attention to buy the product being advertised. For the social practices, the words found in the advertisements are considered have power or control over people. Pond’s advertisements also construct a concept through persuasive linguistic features and visual features. Pond’s advertisements contribute to the construction of an image of ideal beauty in women’s mind through the pictures and texts in which potray a certain beauty concept.